Comparative evaluation of screening tests for maternal and fetal outcome in gestational diabetes - Saxena, Shivi; Khan, Arshiya (International Journal of Research in Medical Sciences, 2017)
Background: We aimed to evaluate the predictive value of two screening tests - 50 gm GCT and 75 gm GTT for adverse maternal and fetal outcome in patients with gestational diabetes mellitus. Methods: This was a prospective study of 200 antenatal women booked at tertiary care hospital Delhi during the year 2010-2012. Pregnant females at 24-28 weeks gestation were randomly selected and subjected to 50 gm GCT and 75 gm GTT. The women’s history, clinical examination recorded, 50 gm GCT and 75 gm GTT values recorded and the two tests were compared for maternal and fetal outcome. Results: 75 gm GTT had higher specificity, positive and negative predictive values as compared to 50 gm GCT for both maternal and fetal outcome. However 50 gm GCT was more sensitive for predicting maternal and fetal complications. Conclusions: 75 gm GTT is better than 50 gm GCT for predicting adverse maternal and perinatal outcome in gestational diabetic patients.